2023
DOI: 10.1002/chem.202302971
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical Scholl Reaction on Phenylated Cyclopentadiene Core: One‐Step Synthesis of Fluoreno[5]helicenes

Gábor Báti,
Dániel Csókás,
Mihaiela C. Stuparu

Abstract: In this study, we explore feasibility of the mechanochemical approach in the synthesis of tetrabenzofluorenes (fluoreno[5]helicenes). For this, commercially available phenylated cyclopentadiene precursors are subjected to the Scholl reaction in the solid state using FeCl3 as an oxidant and sodium chloride as the solid reaction medium. This ball milling process gave access to the 5‐membered ring containing‐helicenes in one synthetic step in high (95‐96%) isolated yields. The solution‐phase reactions, however, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 124 publications
1
3
0
Order By: Relevance
“…In compound 6c, the torsion angle C31–C3–C4–C34 is worth 28°, and this angle is reduced to 23° in fluoreno[5]helicene 6b incorporating tert -butyl instead of methyl para -substituents. These values are in line with those reported in literature for 17-monoaryl- 34 and 17,17-dialkyltetrabenzofluorenes, 38 and the variation of amplitude may be ascribed to the packing force in the crystal. In any case, the racemisation barrier for such helicenic species is low and both enantiomers cannot be separated at room temperature.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In compound 6c, the torsion angle C31–C3–C4–C34 is worth 28°, and this angle is reduced to 23° in fluoreno[5]helicene 6b incorporating tert -butyl instead of methyl para -substituents. These values are in line with those reported in literature for 17-monoaryl- 34 and 17,17-dialkyltetrabenzofluorenes, 38 and the variation of amplitude may be ascribed to the packing force in the crystal. In any case, the racemisation barrier for such helicenic species is low and both enantiomers cannot be separated at room temperature.…”
Section: Resultssupporting
confidence: 92%
“…In addition, on top of their intrinsic properties, propeller-shaped compounds 1 can also be viewed as direct precursors of highly attractive π-extended scaffolds for organic electronics, such as 17,17-diarylcyclopenta[ l , l ′]diphenanthrenes (also referred to as 17,17-diaryltetrabenzo[ a , c , g , i ]fluorenes, Scheme 6 ) and the corresponding spirobifluorenes. 30 b ,33 In this context, Stuparu et al very recently disclosed the successful conversion of pentaphenylcyclopentadiene 2a into 17-phenyl-tetrabenzo[ a , c , g , i ]fluorene upon mechanochemical Scholl reaction, 34 thus improving initial attempts by Dyker et al 35 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 There have been several recent reports on the application of mechanochemical reactions to oxidative coupling reactions of aromatic compounds. 18–27 In 2018, Borchardt et al reported the mechanochemical Scholl reaction, an oxidative cyclodehydrogenation forming aryl–aryl C–C bonds. 18 They established the mechanochemical synthesis of fully planarized PAHs, such as hexa- peri -hexabenzocoronene (HBC) and its larger analogs, from non-planar dendritic oligophenylene precursors using ball mills as reactors.…”
Section: Introductionmentioning
confidence: 99%